Quality characteristics and stability of chicken cutlet fortified with Fish Protein Hydrolysate (FPH) - Raj, Rehana; Varghese, Shiby; Tabassum, Aisha (Fishery Technology, 2020)
Fish Protein Hydrolysate (FPH) was incorporated in chicken cutlet to study its effect on quality aspects and storage stability. FPH was added at four different concentrations viz., 0, 5, 10 and 15%. It was observed that 15% FPH in chicken cutlet gave a better cooking yield of 63.64 Â± 0 .08% and a lower cooking loss of 36.55Â± 0.53%. Hence 15% FPH among the treatment groups was used for the formulation of chicken cutlet with various proportions of chicken and binder (60% chicken and 40% potato, 70% chicken and 30% potato, 80% chicken and 20% potato) for optimization. The combination of 70% chicken and 30% binder exhibited low oil uptake, minimum shrinkage, optimum pH, and overall acceptability during sensory evaluation (OA). Finally, the optimised combination of 70:30 was used to prepare the chicken cutlet and analysed for the storage stability by MAP and Normal Packaging. It was observed that the oxidative parameters such as PV, TBARS and TPC were lower for the samples which were given MAP. OA was highest for the samples with MAP. It could be concluded that FPH imparts a positive impact on storage stability and quality parameters of chicken cutlet.